Effect of mixture proportions on concrete performance. (10th July 2019) - Amini, Kamran; Vosoughi, Payam; Ceylan, Halil; Taylor, Peter
Highlights: At w/cm of 0.35, sorptivity and abrasion resistance of concrete are independent of air content. Regardless of w/cm, increasing the air content results in lower strength and higher shrinkage. Optimum concrete performance can be achieved by paste-to-void volume V p V v ratio of ∼160% Abstract: This paper aims to investigate the relationship between paste ingredients for achieving an optimum paste-to-void volume ratio to meet given performance requirements. To this end, the effect of mixture proportion characteristics, including slag-cement replacement, air-content, water-to-cementitious material ratio (w/cm), and paste volume on concrete performance were evaluated. The performance of the mixtures was evaluated through compressive strength, abrasion resistance, sorptivity, shrinkage, and freeze-thaw resistance measurements. According to the test results, incorporation of slag cement resulted in a significant improvement in concrete performance. In addition, correlation between paste content and concrete properties was found dependent on w/cm, and the maximum desirable paste volume appeared to be about 1.6 times the void content of the combined aggregate system used in this study to achieve optimum performance.